Broadly reactive real‐time reverse transcription‐polymerase chain reaction assay for the detection of human sapovirus genotypes. Issue 3 (15th November 2018) - Oka, Tomoichiro; Iritani, Nobuhiro; Yamamoto, Seiji P.; Mori, Kohji; Ogawa, Tomoko; Tatsumi, Chika; Shibata, Shinichiro; Harada, Seiya; Wu, Fang‐Tzy
Abstract : Sapoviruses are associated with acute gastroenteritis. Human sapoviruses are classified into four distinct genogroups (GI, GII, GIV, and GV) based on their capsid gene sequences. A TaqMan probe‐based real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) assay that detects the representative strains of these four genogroups is widely used for screening fecal specimens, shellfish, and environmental water samples. However, since the development of this test, more genetically diverse sapovirus strains have been reported, which are not detectable by the previously established assays. In this study, we report the development of a broader‐range sapovirus real‐time RT‐PCR assay. The assay can detect 2.5 × 10 7 and 2.5 × 10 1 copies of sapovirus and therefore is as sensitive as the previous test. Analysis using clinical stool specimens or synthetic DNA revealed that the new system detected strains representative of all the 18 human sapovirus genotypes: GI.1‐7, GII.1‐8, GIV.1, and GV.1, 2. No cross‐reactivity was observed against other representative common enteric viruses (norovirus, rotavirus, astrovirus, and adenovirus). This new assay will be useful as an improved, broadly reactive, and specific screening tool for human sapoviruses.